2021
DOI: 10.1115/1.4050323
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Performance Comparison and Augmentation of Two Identical Box-Type Solar Cookers Operating in Tropical Climatic Conditions

Abstract: In the present study, experimental studies have been performed to compare the thermal performance of two geometrically identical box-type solar (B-T-S) cookers. To carry out this aim, the thermal performance of BTS in terms of figure of merits, namely, first figure of merit (F1) and second figure of merit (F2) are calculated for both cooker as specified by the Bureau of Indian standards (BIS). At no load condition (i.e. stagnation test), it is found that first figure of merit for both cookers that is cooker 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The battery then powers the solar tracker and DC motor-pump set, circulating heat transfer fluid via heater plate's heating coil. Arif et al 44 conducted comparative study to investigate the effects of changing position of cooking pot on absorber plate, mirror and aluminium reflector, as well as the number of cooking pots on the performance of two geometrically similar SBCs. Their research found that the lugs helped to reduce heat transfer rate between absorber plate and cooking pot.…”
Section: Introductionmentioning
confidence: 99%
“…The battery then powers the solar tracker and DC motor-pump set, circulating heat transfer fluid via heater plate's heating coil. Arif et al 44 conducted comparative study to investigate the effects of changing position of cooking pot on absorber plate, mirror and aluminium reflector, as well as the number of cooking pots on the performance of two geometrically similar SBCs. Their research found that the lugs helped to reduce heat transfer rate between absorber plate and cooking pot.…”
Section: Introductionmentioning
confidence: 99%